THE EFFECT OF PRICES, BRAND IMAGES, AND AFTER SALES SERVICE REINFORCED BAR STEEL PRODUCTS ON CONSUMER PURCHASING DECISIONS OF PT. KRAKATAU WAJATAMA OSAKA STEEL MARKETING - Rendy Sutiyono; Baruna Hadibrata (Dinasti International Journal of Education Management And Social Science, 2020)
This research aims to determine the effect of Price, Brand Image and After Sales Service of Reinforcing Steel Products on Consumer Purchasing Decisions of PT. Krakatau Wajatama Osaka Steel Marketing. This research was conducted on 265 respondents PT. Krakatau Wajatama Osaka Steel Marketing spread all over Indonesia. The research data collection method uses a questionnaire with SEM (Structural Equation Modeling) data analysis which is described in the Application of Model Evaluation of PLS ??(Partial Least Square) - SEM. The results of this study indicate that the variable price has a positive and significant effect on Purchasing Decisions. Brand Image Variable has positive and significant effect on Purchasing Decisions. While the After Sales Service variable also has a positive and significant effect on Purchasing Decisions.